Från vrångstrupen till fotabjället. Om presentationen av unika konstituenter i Svensk ordbok utgiven av Svenska Akademien - Sköldberg, Emma (Nordiske Studier i Leksikografi, 2007)
The paper presents a study of how unique constituents, by which I mean independent lexemes that occur primarily in a specifi c phrase, are treated in Nationalencyklopedins ordbok (1995–96). I explore aspects of unique constituents including their number, grammatical form when they constitute lemmas, and whether they are possible to defi ne. I also compare how similar words are presented in Den Danske Ordbog (2003–2005). The results will be used to achieve a more stringent presentation of the relevant lexemes in the forthcoming Svensk ordbok utgiven av Svenska Akademien, which is scheduled for release in 2009.